Cooperation Between Actors For Tourism Development: The Apreciation Of Heritage And Cultural Resources In Rural Territories - Amaral, Marta; Figueira, Eduardo (Journal of Tourism, Sustainability and Well-being, 2016)
Framed by the theoretical context concerning cooperation between tourism agents, the present paper aims to contribute for better understanding South Alentejo tourism agents’ perceptions on the areas in which they can cooperate for promoting development and competitiveness in the region. Furthermore, the paper also looks at the tourist agents’ perception on role that the dynamics of cultural resources play in promotion of development and competitiveness in the region. This paper reports results from a case study conducted in the frame of the thesis developed as requirement to get the PhD in Tourism. Data was gathered by a questionnaire developed for the study from a sample of tourism agents working in the public, private business and associative (non lucrative) sectors. The study results has indicated that valuation of the existing culture, integrated development of tourism resources and products and organization of promotional activities are the areas considered more relevant for the tourism agents to cooperate among them. In particular, leaders of different sectors agree with the need to cooperate focusing on the valorisation of local and regional cultural resources. This is important because the South Alentejo region has excellent cultural resources that, if strategically used, can provide a major differentiating factor.